Electrochemical Sensor of Tryptophan Based on an Ag/CP Electrode Prepared by the Filtered Cathodic Vacuum Arc Technique. Issue 3 (1st January 2016) - Fu, Yingyi; Su, Wen; Wang, Tong; Hu, Jingbo
Abstract : A facile filtered cathodic vacuum arc technique was developed to prepare silver film and the film was loaded on carbon paper to form an Ag/CP electrode. This method is convenient, fast and environmentally friendly, and it does not require the use of any other chemicals. The resulting silver film was characterized by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS) and cyclic voltammetry (CV). The experiment results indicate that the silver film was modified on the CP successfully, and the film accelerated the electron transfer rate of the substrate. Cyclic voltammetry (CV) and linear sweep voltammetry (LSV) were employed to evaluate the electrochemical properties of the Ag/CP electrode toward tryptophan oxidation. The Ag/CP electrode exhibited good activity for the electro-oxidation of tryptophan. The oxidation peak currents were proportional to tryptophan concentrations over the range of 0.1 μM to 330 μM. The detection limit was 0.04 μM. In addition, the proposed tryptophan sensor also showed high selectivity with other coexisting species, acceptable reproducibility and long-term stability.